On Whose Authority?: Linguists' Claim of Expertise to Interpret Statutes - Marc R. Poirier (Washington University Law Quarterly, 1995)
This Article sketches some of the ideas and issues involved in the claims of the Law and Linguistics Consortium and others. It focuses mostly on these linguists' claim of interpretive authority, but also on the particular theory of language that they offer. The question of their claim to objectivity also surfaces later in this essay. On all counts, a single inquiry sums it up: On whose terms have these linguists been authorized?
Keywords: Linguistics; Law – Interpretation & amp; construction